2015
DOI: 10.1002/app.43286
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modifications of lignocellulosic materials and their application for removal of cations and anions from aqueous solutions

Abstract: This review discussed the last 10 years progress in the use of lignocellulosic materials chemically modified as low-cost biosorbents. Thus, the chemical modifications, such as chemical pretreatment, oxidation, as well as the grafting of carboxyl groups, amines, amides, etc., on lignocellulosic fibers, that aim to increase the number of adsorption sites and maximize toxic metal ion adsorption capacity have been addressed. The literature presents results that indicated performances of biosorbents equal to or eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 112 publications
0
19
0
Order By: Relevance
“…Conducting bio-sorption experiments were performed by shaking 0.1 g of nSD-KF with 10 mL (1:100 ratio) of phosphate solutions with various concentrations (5,10,20,40,80,160, and 320 mg/L). The agitation was conducted at 400 rpm for 2 h using orbital centrifuge to reach sorbate-sorbent equilibrium.…”
Section: Initial Concentration and Bio-sorption Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conducting bio-sorption experiments were performed by shaking 0.1 g of nSD-KF with 10 mL (1:100 ratio) of phosphate solutions with various concentrations (5,10,20,40,80,160, and 320 mg/L). The agitation was conducted at 400 rpm for 2 h using orbital centrifuge to reach sorbate-sorbent equilibrium.…”
Section: Initial Concentration and Bio-sorption Kineticsmentioning
confidence: 99%
“…Bio-sorption is the use of biomaterials in the removal of pollutants from agricultural wastewater, where the P-loaded bio-sorbent can be reused as compost for land application in the form of supplemental phosphorus fertilizer. For the efficient and cost-saving removal of phosphate from water, the lignocellulosic biomaterials could be used in typical or modified forms [5][6][7]. Woody sawdust is one of these lignocellulosic biomaterial used for this purpose due to its chemical constituents including easily available functional groups such as OH, COOH, and NH 2 , and other compounds such as phenols, alcohols, and aldehydes that are presented in cellulose, lignin, and hemicelluloses.…”
mentioning
confidence: 99%
“…The adsorbed amount decreased with an increasing concentration of electrolytes, especially in the case of cadmium which has the lowest value of Allred-Rochow 3,13,30,38 The presence of anions can lead to the formation of complexes that have a lower affinity for the adsorbent than free metal ions. In their comprehensive review on the use of lignocellulosic materials for the removal of cations from solutions, Melo et al 16 also reported that anions such as Cl 2 have an affinity for metal ions forming soluble and/or insoluble complexes. For example, chloride ions form stable complexes with Zn 21 thus suppressing Zn 21 and Zn(OH) 1 adsorption by the adsorbent.…”
Section: Effect Of the Presence Of Naclmentioning
confidence: 99%
“…Like all agricultural materials, after adsorption hemp-based felt can be incinerated to a much smaller volume of ash and/or recovery of adsorbed metal without adverse impact on the environment. Melo et al 16 reported that lignocellulosic materials form nontoxic sluge that can be easily processed and reused.…”
Section: Eliminationmentioning
confidence: 99%
See 1 more Smart Citation